Some Integrals Involving q-Laguerre Polynomials and Applications - Jian Cao (Abstract and Applied Analysis)
The integrals involving multivariate q-Laguerre polynomials and then auxiliary ones are studied. In addition, the representations of q-Hermite polynomials by q-Laguerre polynomials and their related integrals are given. At last, some generalized integrals associated with generalized q-Hermite polynomials are deduced.